ABH SECRETOR STATUS AMONG THE UNIVERSITY OF CALABAR UNDERGRADUATES, NIGERIA - Etura, Joyce; Abam, John; Akpan, Uwem; Jeremiah, Zaccheaus (Sanamed, 2024)
Introduction: Secretor status is a critical component of human biology that depends on specific glycoproteins in body fluids and secretions. Its importance lies in its significant impact on health and disease, making it a compelling subject for medical research. This study aimed to determine the prevalence and understanding of secretor status among undergraduates at the University of Calabar, Nigeria. The findings could revolutionize our understanding of secretor status and open new research opportunities.Materials and Methods: The study used across-sectional approach, analyzing blood samples from 100 undergraduate students using the adsorption-inhibition method. Most participants were single (94.0%), and the majority were 100-level students (51.0%). 48 students were in the 21 to 28-year range, while 6.0% were 30 or older.Results: The findings of this study are significant, revealing that a substantial proportion of the participants were secretors, 82(82.0%), while 18(18.0%) were non-secretors.Interestingly, most participants (83.0%) were unaware of their secretor status, indicating a potential knowledge gap. Blood group O had the highest number of secretors, 58(96.7%), followed by blood group A 11 (55.0%), blood group B 7(63.6%), and the minor blood group AB 6(66.7%). The most prevalent ethnic group was found among the Efiks (18.1%) followed by Yakurr (16.6%) and the least the Ijaws (3.8%).Conclusion: This study underscores the importance of public education and awareness regarding secretor status and its impact on health and disease
Keywords: Secretor status; glycoproteins; blood groups; undergraduates